Optimizing subject design, timing, and focus in a diversity of engineering courses through the use of a low-cost Arduino shield - Góngora González, Andrés; Fernández-Madrigal, Juan Antonio; Cruz-Martín, Ana María; Arévalo-Espejo, Vicente Manuel; Galindo-Andrades, Cipriano; Sánchez-Garrido, José Carlos; González-Monroy, Javier; Fernández-de-Cañete-Rodríguez, Francisco Javier (IATED, 2020)
This paper describes the design, implementation and evaluation of a novel circuitry that extends the popular Arduino UNO microcontroller board to facilitate multiple educational activities in engineering courses. In particular, the aim of this board, the UMA-AEB, is to minimize the overhead that is usually imposed on the students before they can conduct the actual exercises, yet retain the valuable experiences that could otherwise not be acquired with simulated experiments or inflexible electronic training-benches.
Keywords: Microcontroladores; Microcontroller educational board; Engineering training board; Embedded real-time systems; Control systems engineering